Elatostema perryi a new name for Elatostema humile L.M. Perry (Urticaceae) - Rasingam, L.; Karthigeyan, K. (Phytotaxa, 2019)
The genus Elatostema J. R. Forst. & G. Forst. belongs to the tribe Elatostemateae Gaudich. (1830: 493) of the family Urticaceae. It is one of the largest genera in the family with c. 626 accepted names and mostly distributed from tropical to subtropical regions of Africa, Asia and Oceania (Tseng & Hu, 2015; Lin et al. 2018; Fu et al. 2019). Recently, Tseng et al. (2019) provided a new circumscription for the Elatostema S.l. based on the molecular phylogenetic studies and morphological characters. Perry (1951), while studying the New Guinean flora, described Elatostema humile L. M. Perry (1951: 378) from the Idenburg river of New Guinea. This is a later homonym of the Fijian species Elatostema humile A.C. Sm. (1942: 22) and so illegitimate according to article 53.1 of ICN (Turland et al. 2018). Therefore, a replacement name, Elatostema perryi is proposed here.